The Effects of Radiation Pressure on Orbiting Mirrors with Non-Zero Eccentricity - Bechtel, Hannah Marie (Proceedings of the Wisconsin Space Conference, 2022)
The search for extraterrestrial life has been approached from many angles. For Korpela, et al, among others, the search comes in the form of analyzing stars’ light curves for hints of satellites around exoplanets. Such satellites could be in the form of large, thin, lightweight mirrors, possibly used to redirect sunlight from a star to the surface of a planet. The feasibility and fuel efficiency of such an undertaking would depend heavily on the effects of radiation pressure. My colleagues and I have simulated those satellites using REBOUND (Rein and Liu 2012), an N-body simulator, to understand the effect of radiation pressure on mirrors orbiting an exoplanet. We changed the types of stars, initial orbit orientations, eccentricities, and other variables. Each simulation ran to a pre-set 1000 orbits or until the mirror crashed into the planet or escaped orbit. A list of survival times and other data trends was compiled to identify potentially stable (or quasi-stable) orbits. Overall, it appeared that simulations with initial eccentricity close to zero (0.1, sometimes 0.3) were more like previously investigated initially circular simulations. There were extreme exceptions to this however; some of the initially eccentric simulations lasted for 1000 orbits, while the equivalent initially circular simulations crashed or escaped very early on. We also used the data output from the simulations to create plots like a mirror’s distance from the planet over time and a mirror’s eccentricity over time in order to find possible stability trends. We are still investigating potentially stable configurations.